Statutory Assessment for Special Educational Needs and the Warnock Report; the First 40 Years - Lamb, Brian (Frontiers in Education, 2019)
The Warnock report ‘Special Educational Needs' (Warnock, 1978) provided the catalyst for an enduring framework of individual statutory assessment1 in England for children and young people (CYP) with Special Educational Needs (SEN). Through its implementation in the Education Act (1981), enhanced in the Education Act (1993) and consolidated in the Education Act (1996), the report established the overall SEN framework in England for last 40 years; laying the foundation for statements of SEN and more recently Education, Health and Care Plans (EHCPs). The underlying legal structure has been reinforced with the introduction of the Children and Families Act (2014). However, by establishing the right to specified levels of resource for individual CYP, the Warnock framework has risked undermining adequate provision and parental confidence in the Special Educational Needs and Disability (SEND) framework; a central dilemma of the SEND system. This review considers the development of the statutory assessment system and the consequences of this specific model of securing provision for CYP with complex needs. It also explores the importance of securing parental confidence in the non-statutory offer. While additional legislation to strengthen the SEND framework is desirable the Government could begin to address concerns about the quality of the non-statutory offer through a more rigorous implementation of current legislation linked to reforms in funding, accountability and a renewed focus on rights based legislation in education. The conclusions are focused on the English system but the analysis is relevant to other jurisdiction's assessment, funding, and accountability models.